Building the old time religion : women evangelists in the progressive era - Pope-Levison, Priscilla, 1958- (New York University Press, 2014)
"During the Progessive Era, a period of unprecedented ingenuity, women evangelists built the old time religion with brick and mortar, uniforms and automobiles, fresh converts and devoted protégés. Across America, entrepreneurial women founded churches, denominations, religious training schools, rescue homes, rescue missions, and evangelistic organizations. Until now, these intrepid women have gone largely unnoticed, though their collective yet unchoreographed decision to build institutions in the service of evangelism marked a seismic shift in American Christianity. In this ground-breaking study, Priscilla Pope-Levison dusts off the unpublished letters, diaries, sermons, and yearbooks of these pioneers to share their personal tribulations and public achievements. The effect is staggering. With an uncanny eye for essential details and a knack for historical nuance, Pope-Levison breathes life into not just one or two of these women, but two dozen. The evangelistic empire of Aimee Semple McPherson represents the pinnacle of this shift from itinerancy to institution building. Her name remains legendary. Yet she built her institutions on the foundation of the work of women evangelists who preceded her. Their stories -- untold until now -- reveal the cunning and strength of women who forged a path for every generation, including our own, to follow."--Back cover.